Genetic diversity, population structure and ecological niche modeling of Thyrinteina arnobia (Lepidoptera: Geometridae), a native Eucalyptus pest in Brazil - Nanini, Frederico; Souza, Philipe G. C.; Soliman, Everton P.; Zauza, Edival A. V.; Domingues, Maurício M.; Santos, Fábio A. [UNESP]; Wilcken, Carlos F. [UNESP]; da Silva, Ricardo S.; Corrêa, Alberto S. (Springer Nature, 2024)
Thyrinteina arnobia (Lepidoptera: Geometridae) is a native American species. Despite its historical importance as an insect pest in Eucalyptus plantations, more information is needed regarding the population diversity, demography, and climatic variables associated with its distribution in different regions of Brazil. We used a phylogeographic approach to infer the genetic diversity, genetic structure, and demographic parameters of T. arnobia. We also conducted an ecological niche modeling (ENM) to predict suitable areas for T. arnobia occurrence in Brazil and other countries worldwide. Although T. arnobia populations have low genetic diversity in Brazil, we identified mitochondrial haplogroups predominating in different Brazilian regions and high ФST and ФCT values in AMOVA, suggesting a low frequency of insect movement among these regions. These results indicate that outbreaks of T. arnobia in Eucalyptus areas in different regions of Brazil are associated with local or regional populations, with no significant contribution from long-distance dispersal from different regions or biomes, suggesting that pest management strategies would be implemented on a regional scale. In Brazil, the demographic and spatial expansion signals of T. arnobia seem to be associated with the history of geographical expansion of Eucalyptus plantations, a new sustainable host for this species. ENM indicated that isothermality and annual rainfall are critical climatic factors for the occurrence of T. arnobia in tropical and subtropical areas in the Americas. ENM also suggested that T. arnobia is a potential pest in Eucalyptus areas in all Brazilian territory and in regions from Africa, Asia, and Oceania.
Keywords: Agriculture pest; Eucalyptus brown looper; Maxent model; Population ecology; Population genetics